Pendekatan Komprehensif dalam Pembangunan Sumber Daya Manusia (SDM) Pariwisata Menuju Indonesia Emas 2045 - Tarigan, Hairani; Darmastuti, Shanti; Saraswati, Dini Putri; Nidatya, Nurfarah (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UNIVERSITAS SAPTA MANDIRI, 2026)
Human resources is an important part of supporting the achievement of the vision of a Golden Indonesia 2045. Strengthening human resources is a strong foundation in all sectors, including the development of the tourism sector. Several challenges are still faced in developing competent tourism human resources. Therefore, this research aims to explain the comprehensive approach needed to develop tourism human resources. In-depth interviews and document studies were conducted to obtain data about the importance of developing tourism human resources, the challenges of tourism human resources, and a comprehensive approach to developing tourism human resources. The research results show that approaches in the form of curriculum development in the education sector, occupational mapping within a qualification framework that meets the job market, and cooperation between related parties in developing tourism human resources are very important. A comprehensive approach is important in increasing understanding of the importance of competent human resources in the tourism sector.